Bioinspired wettable–nonwettable micropatterns for emerging applications. Issue 36 (12th August 2020) - Yang, Yuemeng; Xu, Li-Ping; Zhang, Xueji; Wang, Shutao
Abstract : Wettable–nonwettable micropatterns have received tremendous attention due to their unique functionalities. Their emerging applications have been highlighted in this review. Abstract : Superhydrophilic and superhydrophobic surfaces are prevalent in nature and have received tremendous attention due to their importance in both fundamental research and practical applications. With the high interdisciplinary research and great development of microfabrication techniques, artificial wettable–nonwettable micropatterns inspired by the water-collection behavior of desert beetles have been successfully fabricated. A combination of the two extreme states of superhydrophilicity and superhydrophobicity on the same surface precisely, wettable–nonwettable micropatterns possess unique functionalities, such as controllable superwetting, anisotropic wetting, oriented adhesion, and other properties. In this review, we briefly describe the methods for fabricating wettable–nonwettable patterns, including self-assembly, electrodeposition, inkjet printing, and photolithography. We also highlight some of the emerging applications such as water collection, controllable bioadhesion, cell arrays, microreactors, printing techniques, and biosensors combined with various detection methods. Finally, the current challenges and prospects of this renascent and rapidly developing field are proposed and discussed.